Pengaruh Intensitas Penggunaan Gadget Terhadap Perkembangan Sosial Anak Usia 4-5 Tahun di Kober Ciwaka Kecamatan Walantaka - Wahyuni, Sri; Fatimah, Atin; Fahmi, Fahmi (Universitas Pahlawan Tuanku Tambusai, 2025)
The widespread use of gadgets among early childhood has raised serious concerns, due to its potential impact on their social development. This study aims to analyze the influence of gadget usage intensity on the social development of children aged 4–5 years at Kober Ciwaka, Walantaka District. A quantitative method with an ex post facto approach was used. The sample consisted of 30 children selected through purposive sampling. Data were collected using questionnaires and observations and analyzed with simple linear regression using SPSS. The results showed a t-value of -4.098 with a significance level of 0.000 (<0.05), and a correlation coefficient (Beta = -0.612) indicating a strong negative relationship between gadget usage and children's social development. The study concludes that the higher the gadget usage intensity, the lower the children's ability to interact, cooperate, and empathize. Therefore, strict supervision by parents and teachers over gadget usage in early childhood is essential.